Implementation of Reactive Power Markets to Enhance the Power System Network. - Madhuvanthani Rajendran; L. Ashok Kumar (Department of Electrical Engineering, Institut Teknologi Nasional Malang, Indonesia, 2019)
Reactive power is an important component which plays a critical role in maintaining grid reliability, especially voltage stability. The report presents an analysis of the current compensation strategies followed by different independent system operators (ISOs) in US and identifies the drawbacks in the present compensation schemes. The properties of reactive power which poses an impediment to setup a reactive power market has been compared with the need of a reactive power market. Finally, a possible spot market structure has been considered along with bid formulation and its different components as applicable to different reactive power producing equipment.